2013
DOI: 10.1371/journal.pmed.1001401
|View full text |Cite
|
Sign up to set email alerts
|

The Cost and Impact of Scaling Up Pre-exposure Prophylaxis for HIV Prevention: A Systematic Review of Cost-Effectiveness Modelling Studies

Abstract: Gabriela Gomez and colleagues systematically review cost-effectiveness modeling studies of pre-exposure prophylaxis (PrEP) for preventing HIV transmission and identify the main considerations to address when considering the introduction of PrEP to HIV prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
152
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(164 citation statements)
references
References 37 publications
(132 reference statements)
11
152
0
1
Order By: Relevance
“…In this context, a systematic review 76 of the studies that estimated the impact and cost of PrEP on the epidemic showed that the offer of prophylaxis may have a significant impact on the reduction of incidence and be cost-effective, especially if people with higher risk were to be prioritized. In concentrated epidemics 77,78 , even in a scenario of amplification of TasP and moderate changes in sexual practices, the impact of PrEP would be significant, even though the authors warn us that the sensitivity analyses indicated that an unlikely increase in large-scale risk practices would lead to increasing incidence 78 .…”
Section: Prevention For People Who Are More Exposed and Do Not Want Tmentioning
confidence: 99%
“…In this context, a systematic review 76 of the studies that estimated the impact and cost of PrEP on the epidemic showed that the offer of prophylaxis may have a significant impact on the reduction of incidence and be cost-effective, especially if people with higher risk were to be prioritized. In concentrated epidemics 77,78 , even in a scenario of amplification of TasP and moderate changes in sexual practices, the impact of PrEP would be significant, even though the authors warn us that the sensitivity analyses indicated that an unlikely increase in large-scale risk practices would lead to increasing incidence 78 .…”
Section: Prevention For People Who Are More Exposed and Do Not Want Tmentioning
confidence: 99%
“…10 However, it is not always clear what priority these concerns receive in programmes over other considerations such as achieving scale or rolling out new interventions. Finally, new interventions or additions to health programmes have typically been evaluated in isolation [11][12][13] and held in comparison to an estimate of the cost-effectiveness of interventions already funded, an approach that ignores the relative costs and impacts of alternative options. Exceptions in Africa include a national-level cost-effectiveness analysis of prevention portfolios 14 and an exploration of combination prevention in a hyperendemic setting.…”
Section: Introductionmentioning
confidence: 99%
“…Previous economic evaluations have separately examined the cost-effectiveness of PrEP or HIV vaccines in the US, but none have modeled the potential outcomes when combining these products [18][19][20][21][22][23], as shown in a recent review of HIV vaccine cost-effectiveness studies [24]. For treatment of HIV, Truvada® is highly cost-effective when used in combination with other drugs, but the costeffectiveness estimates for prevention are mixed in reviews [21,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…For treatment of HIV, Truvada® is highly cost-effective when used in combination with other drugs, but the costeffectiveness estimates for prevention are mixed in reviews [21,25,26]. If an HIV vaccine is launched in the US, experts may consider modifying PrEP clinical guidelines to inform the most efficient use in combination with HIV vaccines [27].…”
Section: Introductionmentioning
confidence: 99%